PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Desy Natalia Nanda Wicaksono; Dewi Widiana Rahayu; Mohammad Taufiq; Suharmono Kasiyun (Universitas Muhammadiyah Makassar, 2020)
This study aims to analyze the effect before and after the implementation of the Think Pair Share type of cooperative learning model in improving student learning outcomes in elementary school mathematics. The method used in this research is a meta-analysis method. The data collection technique in this research is to browse the articles contained in online journals, using Google Scholar certified by Sinta that has been published in that area. From the subsequent search results, 8 articles published in online journals were taken which will be used as the basis for this study provided there are data before and after the action in the form of scores. The data analysis technique used is descriptive statistics with the Paired Sample T-Test assisted by SPSS 25 Windows. Based on the results of data analysis, the Paired Sample T-Test shows that H0 is rejected and accepts H1 because of the Sig. (2 - tailed) this is 0.001 0.05. Thus, it can be concluded that the application of the Think Pair Share type of cooperative learning model has an effect on student learning outcomes in elementary school mathematics.